SLANG WORDS USED BY MILLENNIAL GENERATION IN INSTAGRAM - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (Jurnal Serunai Bahasa Inggris, 2019)
Indonesia recognizes that Bahasa as a national language which has function as unity language for its society. In fact, the tendency of society especially millennial generation used slang in daily conversation is higher than used Bahasa itself. This study aims to analyse the phenomenon of slang words used by millennial generation in Instagram. The scope of this study is to investigate types of slang used by millennial generation in Instagram, how the meaning of slang words used by millennial generation in Instagram and why millennial generation used slang words in Instagram. Descriptive qualitative research was applied in this study and obtained the data from the discourse of 30 millennial generations in Instagram. The data was obtained from observation, interview and documentation. The result of the data showed that millennial generation used slang words in their communication in Instagram namely there were 31 slang words found in their caption in Instagram. These words contained five types of slang; fresh and creative; flippant; imitative; acronym; and clipping. The millennial generation used slang in Instagram because some reasons such as to address, to initiate relax conversation, to humiliate, to express impression and to show intimacy.    Keywords: Slang, Types of slang, Reasons of slang, millennial generation